Long-term changes in fat distribution in children and adolescents aged 3-18 from Krakow (Poland), within the last 30 years (from 1983 to 2010) - Kryst, Łukasz; Woronkowicz, Agnieszka; Kowal, Małgorzata; Sobiecki, Jan (Anthropological Review, 2018)
In Poland, even in the late twentieth century, the problem of obesity was not significant. However, recent studies have shown an increase in the prevalence of overweight and obesity. Socioeconomic changes, in last decades, approached Poland to Western Europe. A lifestyle of Poles (physical activity and diet) have changed radically. The aim of the study was to investigate changes in adiposity in children and adolescents over the last decades. Two cross-sectional studies were made in 1983 and 2010. The analysis included 10,324 children and adolescents aged 3-18 living in Krakow (Poland). Data on selected skinfolds (triceps, subscapular, abdominal, suprailiac, calf) were collected and compared between the series of studies. The total body fat (sum of 5 skinfolds) was higher in contemporary boys. In girls, there were not noticed such changes. In both sexes, the adiposity of triceps and supscapular region decreased. In the case of abdominal skinfold - there were no significant changes in boys, while contemporary girls had a smaller abdominal adiposity. In boys, there were noticed reduction in suprailiac skinfold thickness. In the case of girls, the reverse trend was reported - contemporary girls were characterized by higher suprailiac adiposity. Children studied in 2010 were characterized by greater calf skinfold. Changes in adiposity are worrying, especially in boys. The priority should therefore be effective prevention and intervention programs. They can prevent further deepening of the problem among Polish children, by the time it will be as severe as in Western Europe.